PENGARUH SOCIAL MEDIA DAN MARKETPLACE MARKETING TERHADAP PERILAKU IMPULSE BUYING DENGAN DIGITAL PAYMENT SEBAGAI MODERATING (Jurnal Riset Akuntansi dan Bisnis Indonesia, 2023)
This research aims to determine the influence of social media and marketplace marketing on impulse buying behavior with digital payment as a moderating. This research was conducted on 100 student respondents in Yogyakarta. They are generation Z active Smartphone users with Social Media and Marketplace when they are shopping in online and also using Digital Payment. The technique sampling that used in this research is non-probability sampling, with a judgment/purposive sampling type. The research method used is a quantitative method and the analytical tool used is SPSS with multiple linear regression analysis techniques and Moderated Regression Analysis (MRA) because this research involves moderating variables. From the results of multiple linear regression analysis, it is proven that Social Media Marketing and Marketplace Marketing have a significant positive influence on Impulse Buying with the significance result of the SM_X1 variable being 0.000 < 0.05 and the significance result of the MP_X2 variable being 0.000 < 0.05. However, the results of the MRA analysis on the Digital Payment moderation variable were not able to moderate the influence of the Social Media Marketing and Marketplace Marketing variables on the Impulse Buying variable because the results of the significance of the interaction variable were > 0.05.
Keywords: Social Media, Marketplace; Digital Payment; Impulse Buying; Moderating.